Compliance with hand sanitizer quality during the SARS-CoV-2 pandemic: Assessing the impurities in an ethanol plant. (1st November 2021) - Cohen, Gabriel; Kreutzer, Nathan; Mowat, Katie; Aly Hassan, Ashraf; Dvorak, Bruce
Abstract: Using alcohol-based disinfectants is an effective method for preventing the spread of COVID-19. However, non-traditional manufacturers of alcohol-based disinfectants, such as ethanol plants, need to undergo additional treatment to curb their impurities to limits set by the Food and Drug Association (FDA) to produce alcohol-based disinfectants. To transform them to disinfectant-grade alcohol, 17 process streams in a dry-mill ethanol plant were analyzed to determine the quality parameters for acetaldehyde, acetal, propanol, methanol, and water, including chemical oxygen demand, total suspended solids, and nutrients. Results suggest that the process stream generated by the distillation column requires further treatment because the acetaldehyde and acetal concentrations are significantly higher than the impurity limit set by the FDA. The addition of a second distillation column could be a potential method for addressing impurities and it will have minimal influence on hazardous air pollutant generation and water use. Graphical abstract: Image 1 Highlights: Measured impurities in process streams within an ethanol plant. Impurities magnified at Distillation Column Tops, Molecular Sieve Reject, Fermentation Tank, and Beer Well. Plant modifications will not change the emissions of hazardous air pollutants. Removing impurities will increase greenhouse gas emissions by 5%–10%.